2019
DOI: 10.21640/ns.v11i23.2093
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de dos métodos de secado en los compuestos fenólicos totales, L-DOPA y la actividad antioxidante de Vicia faba L.

Abstract: La L-DOPA es uno de los metabolitos secundarios presentes en las leguminosas, como Mucuna pruriens y Vicia faba L., su contenido se puede ver afectado por el método de secado, variedad y estado de desarrollo de la planta. El objetivo de este estudio fue analizar el efecto del método de secado por estufa y por liofilización en el contenido de compuestos fenólicos totales (CFT), de L-DOPA y de la actividad antioxidante en plántulas y en flor de dos variedades de haba. Dos variedades de haba, Diamante y Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The variety Rojita had the highest antioxidant activity (IC 50 = 87.68 µg mL −1 ), which was significantly different (p ≤ 0.05) from the varieties José María and Matlazinca (Table 1). Ortiz et al [14] reported antioxidant activity in plant extracts of broad bean varieties 20 DAE that were lower than those reported in our study (Diamante IC 50 = 121.04 µg mL −1 and Zac-22 IC 50 = 130.27 µg mL −1 ). The antioxidant activity of the broad bean plant extract can be attributed to the high content of L-DOPA; a study [17] revealed that in extracts from broad bean sprouts this metabolite contributed strongly to antioxidant activity, unlike kaempferol glucosides.…”
Section: In Vitro Antioxidant and Anti-inflammatory Activitycontrasting
confidence: 94%
See 3 more Smart Citations
“…The variety Rojita had the highest antioxidant activity (IC 50 = 87.68 µg mL −1 ), which was significantly different (p ≤ 0.05) from the varieties José María and Matlazinca (Table 1). Ortiz et al [14] reported antioxidant activity in plant extracts of broad bean varieties 20 DAE that were lower than those reported in our study (Diamante IC 50 = 121.04 µg mL −1 and Zac-22 IC 50 = 130.27 µg mL −1 ). The antioxidant activity of the broad bean plant extract can be attributed to the high content of L-DOPA; a study [17] revealed that in extracts from broad bean sprouts this metabolite contributed strongly to antioxidant activity, unlike kaempferol glucosides.…”
Section: In Vitro Antioxidant and Anti-inflammatory Activitycontrasting
confidence: 94%
“…The highest levels, though statistically equal (p ≤ 0.05), were detected in the varieties Matlazinca (135.63 mg GAE g −1 DM) and Rojita (131.65 mg GAE g −1 DM) (Table 1). These values are higher than those reported by Ortiz et al [14] (94.16 mg GAE g −1 DM). It seems that the TPC content in the plant is higher than that in broad bean seed analyzed in other studies.…”
Section: Total Phenolic Compounds and Total Flavonoidscontrasting
confidence: 71%
See 2 more Smart Citations